Sedentary: A Healthy Lifestyle App for Home Office Workers - Mauricio, David; Flores-Cortegana, César Marcelo; Shuan-Arias, Anthony Jaimar; Castañeda, Pedro; Rojas-Mezarina, Leonardo; Castillo-Sequera, José Luis (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Although home office employment has been happening for several decades, the COVID-19 pandemic has led to an unprecedented surge in telework. Concurrently, the prevalence of sedentary individuals has gradually increased, posing health challenges. In this study, we introduce a mobile app designed to promote healthy lifestyles (HLs) among home office workers (HOWs). Central to this app is an IBM Watson Assistant-powered Chatbot, offering remote workers a near-natural interface to enhance their well-being. Users can establish lifestyle improvement goals, receive activity reminders, earn rewards upon achieving goals, and employ their smartphone’s pedometer to measure their physical activity (PA) levels. Additionally, the app includes questionnaires to gauge the user’s knowledge on sedentarism and HL. The app’s efficacy was assessed via a two-week trial involving 20 participants. The results showed that HL knowledge was improved in 46% of the users. Usability surveys yielded high ratings in terms of usefulness, user-friendliness, and recommendations.